Green roof, a solution to reduce environmental pollution and sustainable urban development - Saba Hosseinpour; Bint Alhoda Izadi Kahkesh; Sahar Toofan (آلودگی‌های محیطی و توسعه پایدار شهری)
A green roof, also known as a garden roof, vegetable roof, or biological roof, is an engineering system that enables the growth of plants on roof and facade, offering numerous advantages. Therefore, many countries, particularly those in North America and Western Europe, have developed regulations, executive rules, and mandatory instructions for green infrastructure. However, in many large cities, the implementation of such systems remains clearly insufficient. The benefits of green roofs include camouflage, concealment and deception, energy conservation, building sustainability, aesthetic enhancement, shaping and changing shape, environmental assimilation, shape flexibility, natural consequence control (e.g. floods and water runoff), environmental preservation, water pollution protection, increased green space per capita, improved societal psychological atmosphere, sound and heat insulation, extended lifespan of roof and facade insulation, reduced energy consumption, food production cycle, air quality improvement (reducing carbon dioxide and increasing oxygen), and damage control from storms and heavy rainfall. This article discusses the types of green bodies, their executive details, and their general advantages, primarily in soft defense and their specific advantages in passive defense and their role in large urban areas.